2014
DOI: 10.1007/s11307-014-0811-7
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed Development of Striatal Dopamine Transporters in Fatty Versus Lean Zucker Rats: a Follow-up Small Animal PET Study

Abstract: Maturation of the striatal dopamine innervation is impaired in this model of obesity/hyperlipidaemia without diabetes, implying an acquired trait of reduced dopamine reuptake capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…We also measured the DAT density availability at baseline and on day 14 of HAL treatment (follow-up). Pairs of BP ND maps were calculated relative to the cerebellum TAC, as documented in our previous characterization of this DAT ligand [20,23].…”
Section: Micropet Brain Studymentioning
confidence: 99%
“…We also measured the DAT density availability at baseline and on day 14 of HAL treatment (follow-up). Pairs of BP ND maps were calculated relative to the cerebellum TAC, as documented in our previous characterization of this DAT ligand [20,23].…”
Section: Micropet Brain Studymentioning
confidence: 99%
“…Comparisons of rats using PET or single-photon emission computerized tomography have also shown reduced DAT density in older rats [24,25]. However, in a study using DAT PET, Cumming et al showed that the binding potential in the striatum of Zucker rats was higher at 6 months of age than at 6 weeks of age [26]. This conflicting result suggests that the binding potential at 6 weeks of age was a greater influence than age-related decline in DAT expression at 6 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, few imaging studies have been reported on alterations in the central nervous system of T2DM models, including [ 18 F]FP-CMT for dopamine innervation[44] and [ 18 F]FDG for metabolism. Cognitive impairment, cortical thinning, and hippocampal synaptic reorganization have been observed in T2DM rats [6].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, few imaging studies have been reported on alterations in the central nervous system of T2DM models, including [ 18 F]FP-CMT for dopamine innervation [44] and [ 18 F]FDG for metabolism.…”
Section: Discussionmentioning
confidence: 99%